The average performance analysis of a closest-pair algorithm - Chang, R. C.; Lee, R. C. T. (International journal of computer mathematics, 1984)
Bentley proposed a divide-and-conquer approach to solve the planar closest pair problem. In this paper, we shall show that the average case performance of this algorithm is proportional to the number of poins being examined.